Mangrove Biodiversity of Bunaken National Park in Project-Based Learning to Improve Students’ Competitive Skills during the COVID-19 Pandemic - Wurarah, Masje; Semuel, Mokosuli Yermia; Sumampouw, Herry Maurits (Jurnal Pendidikan Progresif, 2022)
Mangrove Biodiversity of Bunaken National Park For Project-Based Learning To Improve Competitive Student Skills During The COVID 19 Pandemic. College graduates in the era of the industrial revolution 4.0 are required to have strong competitive abilities. Competitive skills can be measured from the science process skills possessed. Objectives: This study aims to obtain a competitive profile of students' skills through a project-based learning method on mangrove biodiversity in Bunaken National Park, North Sulawesi. Methods: The research subjects were students who took Sulawesi biodiversity courses in 2020/2021. Fourteen science process skills were measured using a rubric Findings: The results showed that students' mastery of science process skills was high in the Sulawesi biodiversity course. Conclusion: . The application of project-based learning to the problem of mangrove biodiversity in Bunaken National Park can induce students to develop problem-solving skills, collaboration, creativity, and literacy skills. Keywords: biodiversity mangrove, competitive skills, project-based learning.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202219